Botulinum toxin type A for pain control in temporomandibular joint disorder patients - Khounganian, Rita M.; Mahdi, Abdulaziz A.; Aloshaywi, Abdulaziz K.; Almanqur, Ahmed I. (International Journal Of Community Medicine And Public Health, 2024)
Temporomandibular disorders (TMDs) include different conditions, such as: myofascial pain that involves discomfort or pain in the muscles that control jaw function, also internal derangement of the jaw involves a displaced disc, or injury to the condyle, and arthritis that refers to a group of degenerative/inflammatory joint disorders, the causes of TMDs is multifactorial; it includes occlusal factors such as bruxism, stress and psychological status, hormonal factors, and systemic diseases, treatment encompasses simple treatment for example physiotherapy, intra-oral appliance, certain medications, as well as complex treatment such as intra-articular injection and surgery. Botox is considered a peripheral muscle relaxant and a very effective option to reduce pain with TMD patients. Consequently, the present review article was undertaken to shed some light on the different treatment modalities of TMDs and specifically the relevance of botulinum toxin type A (BTX-A) for pain relief in TMD patients. Searches were conducted in Medline (via PubMed, Scopus, The Cochrane library), all original relevant studies that discussed the effectiveness of BTX-A in managing temporomandibular disorders were included. BTX-A injection in masticatory muscles of patients with TMD can be a useful supportive therapy to control pain and improve quality of life.